Loanwords: Typology and Adaptation - Abdurahimova Mahliyo; Isakova Nodira Azzamovna (Indonesian Journal Publisher, 2026)
This article explores the phenomenon of loanwords from a typological and functional perspective, analyzing the main types of lexical borrowing and the mechanisms of their adaptation in the recipient language. The study examines the linguistic, sociocultural, and pragmatic factors that motivate borrowing processes, with particular attention to phonetic, morphological, semantic, and orthographic integration. Drawing on examples from languages such as English, Uzbek, and Russian, the article identifies structural patterns of direct borrowings, calques, hybrid formations, and semantic loans. The article also highlights the role of loanwords in lexical enrichment, terminological development, and stylistic variation. It concludes that typological classification of loanwords and analysis of their adaptation strategies provide valuable insights into language contact phenomena and contribute to broader studies in sociolinguistics, comparative linguistics, and translation studies.